Oued Souf (Algerian Sahara): balancing rising groundwater and agricultural sustainability - Diaf, Imene; Lifa , Assia; Mostfaoui, Amar (Bulletin of Geography. Physical Geography Series, 2024)
This research addresses the issue of rising groundwater in the Algerian Sahara, a paradoxical phenomenon given that the desert is typically associated with dryness. The cause of this rising water is the recharge of aquifers by wastewater from local activities resulting from poor water resource management. This has led to overexploitation of water resources in Oued Souf, posing an environmental threat and agricultural loss in the Ghouts. To sustainably manage these resources, it is essential to establish a management system involving all relevant stakeholders. Ultimately, sustainable groundwater management requires effective management of Sahara aquifers. This involves avoiding overuse and overexploitation, limiting excessive pumping, employing artificial recharge methods to replenish water reserves, and regulating water flows in watersheds to reduce rising water levels in the Sahara.